2020
DOI: 10.1021/acsabm.9b00985
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ion Transport by PITENINs across the Phospholipid Bilayers of Vesicles and Cells

Abstract: Small-molecule-based Cl − ion carriers are gaining revived attention because of their recently discovered role toward anticancer activity. Herein, we showed that the anticancer agents, PITENINs, have an efficient transmembrane Cl − ion transport activity. Theoretical calculations, 1 H NMR titration, and spectrophotometric analysis suggest that the PITENINs strongly bind with a Cl − ion. In addition to the lipophilicity, the presence of both acylthiourea and phenolic OH moieties of the compounds plays a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As part of our drug discovery program, we are engrossed in developing novel strategies to fight against cancer and other diseases. Recent studies by several groups revealed that synthetic Cl – ion transporters are potent compounds to fight against cancer and other ion transport-related diseases. Earlier, we also demonstrated that bis­(iminourea), PITENINS, and diphenylethylenediamine derivatives are selective Cl – ion carriers and promote apoptosis-mediated cell death. ,, In particular, the bis­(iminourea) and PITENINS derivatives showed pH-dependent Cl – ion transport activities. , Herein, we showed that potent quinine derivatives selectively transport Cl – ions across the lipid bilayers. A series of reported biophysical measurements and biological activity studies including 1 H NMR titration, DFT analysis, HPTS and chloride ion-selective electrode-based ion transport measurements, FCCP and valinomycin-based mechanistic studies, U-tube assay, leaching test, vesicle leakage assay, MTT assay, and western blotting assay were performed. ,, In addition, various new biophysical, biological activity, and in vivo studies were performed to investigate the efficiency of quinine derivatives in promoting Cl – -ion-mediated anticancer activities.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…As part of our drug discovery program, we are engrossed in developing novel strategies to fight against cancer and other diseases. Recent studies by several groups revealed that synthetic Cl – ion transporters are potent compounds to fight against cancer and other ion transport-related diseases. Earlier, we also demonstrated that bis­(iminourea), PITENINS, and diphenylethylenediamine derivatives are selective Cl – ion carriers and promote apoptosis-mediated cell death. ,, In particular, the bis­(iminourea) and PITENINS derivatives showed pH-dependent Cl – ion transport activities. , Herein, we showed that potent quinine derivatives selectively transport Cl – ions across the lipid bilayers. A series of reported biophysical measurements and biological activity studies including 1 H NMR titration, DFT analysis, HPTS and chloride ion-selective electrode-based ion transport measurements, FCCP and valinomycin-based mechanistic studies, U-tube assay, leaching test, vesicle leakage assay, MTT assay, and western blotting assay were performed. ,, In addition, various new biophysical, biological activity, and in vivo studies were performed to investigate the efficiency of quinine derivatives in promoting Cl – -ion-mediated anticancer activities.…”
Section: Resultsmentioning
confidence: 78%
“…The pH-dependent selective transport of ions by small synthetic molecules has already been applied to explore the benefits of the acidic extracellular microenvironment of the tumor cells in comparison with that of healthy cells. However, the biological activities of these pH-sensitive synthetic Cl – ion transporters were not thoroughly investigated. …”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in another instance, phosphatidylinositol-3,4,5-trisphosphate (PIP3) inhibitors (PITENINs) functioning as synthetic Cl À ion transporters in the phospholipid bilayers were demonstrated. 237 The specific binding of Cl À to PITENINs was confirmed by 1 H NMR titration, as well as the DFT calculations. Cl À transport activity depends on the cholesterol concentration, suggesting that PITENINs are the carriers for Cl À ions transmembrane conduction via the H + /Cl À transport pathway.…”
Section: Proton Selectivitymentioning
confidence: 78%
“…59 Recent studies have revealed that selective transport of chloride ions by ion carriers can break the balance of pH and undermine the ionic homeostasis of cells, inducing apoptosis in cancer cells. 59,237 Therefore, Cl À -selective channels can be a potential candidate for apoptosis-inducing cell death. Supramolecular barrel-rosette chloride ion channels were used to mediate the transport of Cl À into cells.…”
Section: Apoptosis-inducing Cell Death or Cancer Treatmentmentioning
confidence: 99%
“…The transport and biological activities of the acylthiourea based phosphatidylinositol-3,4,5-trisphosphate (PIP3) inhibitors (PITENINs) were reported by the same research group recently (Figure 13B). [50] Among these PITENINs, 47 a (PIT-1) and 47 b (DM-PIT-1) displayed significant Cl À transport ability. The cell viability test on HeLa cell suggested that compounds 47 a and 47 b disrupted the Cl À ion homeostasis and promoted cell death via apoptotic pathway.…”
Section: Acyclic Anionophores Based On Urea and Thioureamentioning
confidence: 96%